Development of articulate storyline learning media to improve biology learning outcomes for junior high school students - Ifanny Nurhayatus Saadah; Samsun Hadi; Mochammad Agus Krisno Budiyanto; Abdulkadir Rahardjanto; Atok Miftachul Hudha (Research and Development in Education (RaDEn), 2022)
Learning media is an important key to the success of learning to lead to student interaction with learning resources so that goals can be achieved, one of which is in biology lessons in junior high school. The purpose of this study was to produce a product in the form of learning media using Articulate Storyline software, in which to determine an increase in student learning outcomes in class VIII Junior High School (SMPN) 5 Malang. This study uses Research and Development (R&D) research by using the Borg & Gall model which has 10 steps. The use of the Borg and Gall R&D model in this research uses 7 steps, namely: (1) Potential and Problems, (2) Data Collection, (3) Product Design, (4) Design Validation, (5) Design Revision, (6) Test Try the Product, (7) Product Revision. To find out whether there is an increase in learning outcomes, trials are carried out on a small-scale test and extensive-scale test, students are given a pretest and posttest to measure the effect of using media on learning outcomes. Based on test results from media experts it was declared feasible, effective, and efficient for use in learning. Based on the results of the paired t-test with significant. The results of calculations using SPSS, obtained a P value <0.05, which means that there is a significant difference between the average pretest and posttest scores between before and after using the Articulate Storyline learning media or it can be said to improve student learning outcomes.